Voltage-Gated Potassium Channel Kv1.3 as a Target in Therapy of Cancer - Teisseyre, Andrzej; Palko-Labuz, Anna; Sroda-Pomianek, Kamila; Michalak, Krystyna (Frontiers in Oncology, 2019)
Voltage-gated potassium channel Kv1.3 is an integral membrane protein, which is selectively permeable for potassium ions and is activated upon a change of membrane potential. Channel activation enables transportation of potassium ions down their electrochemical gradient. Kv1.3 channel is expressed in many cell types, both normal and cancer. Activity of the channel plays an important role in cell proliferation and apoptosis. Inhibition of Kv1.3 channel may be beneficial in therapy of several diseases including some cancer disorders. This review focuses on Kv1.3 channel as a new potentially attractive molecular target in cancer therapy. In the first part, changes in the channel expression in selected cancer disorders are described. Then, the role of the channel activity in cancer cell proliferation and apoptosis is presented. Finally, it is shown that some low molecular weight organic inhibitors of the channel including selected biologically active plant-derived polycyclic compounds may selectively induce apoptosis of Kv1.3-expressing cancer cells while sparing normal cells and healthy organs. These compounds may be promising candidates for putative application in therapy of some cancer disorders, such as melanoma, pancreatic ductal adenocarcinoma (PDAC) or B-type chronic lymphocytic leukaemia (B-CLL).